A history of astrology, divination and prophecy - Campion, Nicholas; Edge, Joanne; Farnell, Kim; Gazur, Ben; Koch, Ulla Susanne; Kotyk, Jeffrey; Lootah, Mai; Murray, Cailín; Nde, Helen; Parker, Philip, 1965-; Pfeffer, Michelle; Konkel, Izabela Podlaska; et al. (DK Publishing, 2025)
"A History of Astrology, Divination & Prophecy traces the journey of astrology from its roots in the 3rd century BCE, when ancient Mesopotamians studied celestial bodies with the aim of predicting the future, and its development into the distinct branches of Eastern astrology, Hindu (Vedic) astrology, and Western astrology that we know today. Learn about the numerous techniques that have been devised over the centuries to predict the future--from the use of yarrow stalks in the I Ching more than 2,500 years ago to methods still practiced today, such as tarot, crystals, palmistry, and numerology. Discover the story of influential and learned seers, from the oracles of Ancient Greece to the 16th-century French philosopher and mystic Nostradamus, who is said to have predicted the death of Queen Elizabeth II, and explore how our fear of and fascination with astrology, divination, prediction, and prophecy have been depicted in art and literature." --